2015
DOI: 10.1107/s1600576715011206
|View full text |Cite|
|
Sign up to set email alerts
|

The ash heap of crystallography: restoring forgotten basic knowledge

Abstract: A critical analysis of some basic notions often overlooked in crystallographic education is presented to correct some common oversights occurring both in the literature and in textbooks. The crystal forms (face forms), defined in terms of their geometric eigensymmetry, are 47 in number, not 48 as often found in the literature. The split of the dihedron into dome and sphenoid calls for the consideration of the physical properties of the faces building a form; in that case, however, the same criterion should be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 12 publications
(10 reference statements)
0
44
0
Order By: Relevance
“…In the case of centred cells, however, such a simplification is incorrect, inconsistent with the definition of these indices and a potential source of error. After addressing specifically the case of Miller indices in our previous article (Nespolo, 2015a), we have shown that the same type of problem concerns also crystallographic direction indices: these are actually restricted to rational values. We hope that our analysis will help avoid mistakes and oversights by crystallographic software developers and the end users of such software and draw the attention of crystallography lecturers to the necessity to make students well aware of the consequences of adopting centred cells, which may seem trivial but are actually too often overlooked.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of centred cells, however, such a simplification is incorrect, inconsistent with the definition of these indices and a potential source of error. After addressing specifically the case of Miller indices in our previous article (Nespolo, 2015a), we have shown that the same type of problem concerns also crystallographic direction indices: these are actually restricted to rational values. We hope that our analysis will help avoid mistakes and oversights by crystallographic software developers and the end users of such software and draw the attention of crystallography lecturers to the necessity to make students well aware of the consequences of adopting centred cells, which may seem trivial but are actually too often overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…As we have pointed out (Nespolo, 2015a), this is true only when a primitive unit cell is adopted, whereas in the case of multiple unit cells this condition no longer applies and is replaced by characteristic relations between Miller indices that correspond to the integral reflection conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The first edition of this book, published in 2010, was reviewed by Nespolo (2012). I describe here only the changes with respect to the previous edition.…”
mentioning
confidence: 99%
“…Bragg's law, structure factors. The presentation is affected by the common mistake of considering Miller indices to be restricted to relatively prime indices independently from the basis vectors chosen (see a discussion in Nespolo, 2015), which leads to the selfcontradictory use of both (100) and (200) notation to indicate different planes of the same family. From a single example (bcc structure) the integral reflection conditions are introduced without further explanation; zonal and serial conditions are not mentioned.…”
mentioning
confidence: 99%
“…In fact, the projection of a b-unique mB unit cell (equivalent to mP) is incorrectly labelled mC (the in-plane angle should have been right to get an mC unit cell) and the 'trigonal' (which does not exist: read 'rhombohedral' instead) unit cell is shown without any centring nodes, which means that the hP unit cell is shown twice. Miller indices (the correct ones: indices of lattice planes) are given as h 1 ; h 2 ; h 3 instead of h; k; l and are incorrectly defined as never containing common factors, which is true only for primitive (Nespolo, 2015). The screw or glide component of the corresponding screw rotations and glide reflections are said to be 'rational fractions' of a period, which is true for the defining operation of a screw axis or glide plane, but certainly not in general (hint: how would you describe a rotation followed by an integer translation parallel to the axis and relating atoms in different unit cells?).…”
mentioning
confidence: 99%